2016
DOI: 10.4324/9781315473895
|View full text |Cite
|
Sign up to set email alerts
|

Sanity, Madness and the Family

Abstract: Laing and Esterson describe an investigation of 11 patients suffering from ronic or acute and episodic schizophrenia, and of their families. Patients and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 0 publications
0
30
0
7
Order By: Relevance
“…Laing and Cooper shared the premise that people develop their personal identities by virtue of being reflected in the attitudes of other people and society in general (Cooper, 1971;Laing, 1967). Especially in The Divided Self, Laing (1960) contrasts the social stability that signifies the ontologically secure individual with those individuals with unstable relationships -family in particular -owing to so-called double binds: paradoxical demands forced on the individual by social circumstances (Laing and Esterson, 1971). Psychiatry contributes to destabilizing the sense of identity by reducing psychological problems to inherited biological diseases, rather than treating them at the psychological level.…”
Section: The Legacy Of Anti-psychiatrymentioning
confidence: 99%
“…Laing and Cooper shared the premise that people develop their personal identities by virtue of being reflected in the attitudes of other people and society in general (Cooper, 1971;Laing, 1967). Especially in The Divided Self, Laing (1960) contrasts the social stability that signifies the ontologically secure individual with those individuals with unstable relationships -family in particular -owing to so-called double binds: paradoxical demands forced on the individual by social circumstances (Laing and Esterson, 1971). Psychiatry contributes to destabilizing the sense of identity by reducing psychological problems to inherited biological diseases, rather than treating them at the psychological level.…”
Section: The Legacy Of Anti-psychiatrymentioning
confidence: 99%
“…The research compiled in Sanity, Madness and the Family was never intended to sit as a singular entity. In a draft paper for the second edition of the text, Laing and Esterson (1964a) revealed that it was supposed to be the first part of three volumes of study on the subject of family and schizophrenia, with volume two containing a critical examination of other studies of families in relation to psychosis, and volume three a study of a contrast group of ‘ordinary’ families. Here they underlined the conclusions already revealed by the previous study, proposing the need to push further into the realms of families deemed ‘normal’ to uncover a contrast between them and the families of schizophrenics.…”
Section: Imagining Spaces Of ‘Asylum’mentioning
confidence: 99%
“…Here they underlined the conclusions already revealed by the previous study, proposing the need to push further into the realms of families deemed ‘normal’ to uncover a contrast between them and the families of schizophrenics. Laing and Esterson hoped not only to develop theoretical thinking about families in general by composing ‘ideographically, individual pictures or gestalts of each family we study’ (Laing and Esterson, 1964a: 8), but also to develop a method that would allow them to detect the differences between the families under consideration. One aspect of this method was to create an audio-visual record of the families, for they were as interested in what they could see as what they could hear (p. 13).…”
Section: Imagining Spaces Of ‘Asylum’mentioning
confidence: 99%
See 1 more Smart Citation
“…88-91). Laing και οι οπαδοί του(Laing & Esterson, 1964, σελ. 52), προερχόμενοι από το χώρο της ψυχικής υγείας σκιαγραφούσαν την οικογένεια ως τον κακόβουλο «προγραμματιστή» των ψυχώσεων και των αποκαλούμενων «φυσιολογικών» ενηλίκων που πλαισιώνουν την κοινωνία.…”
unclassified